Estado nutricional e avaliação de caracteres secundários da produção em dois clones jovens de seringueira em São José do Rio Preto, SP - Cavalcante, Juliane Ribeiro [UNESP]; Conforto, Elenice de Cassia [UNESP] (My University, 2013)
This work had as objective compare both secondary traits in the production and nutritional status of the rubber tree clone Fx 3864 to the RRIM 600, already established in the São Paulo Western Plateau, in order to contribute with the indication of a potentially alternative clone to be planted in this area. In the ages among 04 and 27 months after planting, there were periodically measured plant height, stem perimeter, leaf area, canopy diameter in the line and between the line of planting, bark thickness, dry mass of stem and leaf and specific leaf mass. The clone RRIM 600 highlighted in height; however, Fx 3864 presented larger canopy diameter in the line and between the line. The bark thickness was similar in both clones during the study period. After 22 months of plantation there hadn’t been significant differences in the values of canopy diameter and leaf area. The leaf area analysis 17 months following the plantation revealed adequate nutritional values for both clones. Considering the evaluated characters, the performance of the clone Fx 3864 was equal to the RRIM 600 during the first 27 months of cultivation.

Este trabalho teve como objetivo comparar os parâmetros secundários da produção e o estado nutricional do clone Fx 3864 ao do RRIM 600, já estabelecido no Planalto Ocidental Paulista, para contribuir na indicação de um clone potencialmente alternativo para o plantio nesta região. Nas idades entre 04 e 27 meses após o plantio, foram avaliados periodicamente a altura da planta, perímetro do caule, área foliar, diâmetro da copa na linha e na entrelinha de cultivo, espessura da casca, massa seca do caule e da folha e massa específica foliar. O clone RRIM 600 destacouse em altura; no entanto, Fx 3864 apresentou diâmetro da copa na linha e na entrelinha maiores. A espessura da casca foi semelhante entre os clones durante todo o período de estudo. A partir dos 22 meses após o plantio, não foram verificadas diferenças significativas nos valores de perímetro do caule e área foliar. A análise foliar aos 17 meses após o plantio revelou valores nutricionais adequados para ambos. Considerando os caracteres avaliados, o desempenho do clone Fx 3864 foi equivalente ao do RRIM 600 durante os vinte sete primeiros meses de cultivo.
Secondary traits in the production and nutritional status of two young rubber tree clones in São José do Rio Preto, SP, Brazil
Keywords: RRIM 600; Fx 3864; altura; diâmetro da copa; espessura da casca; height; canopy diameter; bark thickness